A systematic review on the formative assessment practice in teaching and learning in secondary school - Halimah Abd Halim; Mohd Isa Hamzah; Hafizhah Zulkifli (Institute of Advanced Engineering and Science, 2024)
Formative assessment is an assessment that is conducted throughout the teaching and learning process. Therefore, teachers should play an important role in mastering the appropriate approaches to practicing formative assessment. According to previous studies, some teachers are unable to comprehend the roles of formative assessment practices in teaching and learning, which prevents them from using them effectively in the classroom. Many researchers have conducted research related to the practice of formative assessment in schools due to this issue. Therefore, this article aims to conduct a systematic literature review (SLR) on past studies related to the practice of formative assessment in teaching and learning in secondary schools. This SLR writing process has been referred to as the Preferred Reporting Items for systematic review and meta-analysis (PRISMA) writing standard. To find related articles and resources in this systematic literature review, two main databases, namely Web of Science and Scopus, were used. A total of 19 articles were extracted from 366 from 2017 to 2021, with exceptions and inclusion criteria considered. Based on the theme analysis, this SLR has three main themes: assessment diversity; assessment strategies, and student learning development. Thus, this study suggests that all compulsory levels of education understand formative assessment conceptually and its implementation comprehensively. This can be disseminated through teacher professional development training programs. It is hoped that such programs will develop teachers who are committed to integrating the concept and practice of assessment for the benefit of students in twenty-first century education.